Multi-Disciplinary Simulation Training for Anaesthetic Practitioners. Issue 7 (July 2013) - Hughes, Rob
A multi-disciplinary simulation training course devised and implemented at Morriston Hospital is described. The participants in the simulation exercise included both medical and non-medical professionals in a pilot study intended to analyse the effectiveness of a multi-disciplinary approach to this training technique. Questionnaires completed by the participants both immediately after the training session and again some months later highlight the desirability of this multi-disciplinary training. The success of the training course and the lessons learned from its implementation are being used to plan a similar second session in the near future.